Economic stagnation and inequality: new theoretical and empirical perspective - Sung-Hee Jwa; Taekyu Lee (Digital Economy and Sustainable Development)
Abstract This paper argues that economic discrimination (ED) can promote shared and inclusive growth when instituted by the trinity of economic development, market, corporation, and government. In contrast, Economic Egalitarianism (EE) will work against it. ED means treating economic differences differently, while EE means treating economic differences equally or indifferently. As a pinnacle of ED institutions in the capitalist economy, corporate organizations play a crucial role in shared and inclusive growth. An empirical study utilizing cross-country panel data and time series data for the US and Korea shows: 1) Income grows with corporate growth but declines with the extent of the EE-based redistributive welfare state. 2) Income distribution improves with corporate growth but worsens with the extent of the EE-based redistributive welfare state. 3) Income distribution coevolves with income growth. These results imply that a polarized economic stagnation may be due to stagnation of corporate growth and an overrun redistributive welfare state lacking ED incentives. The sustainable redistributive welfare state in capitalism can be attainable only by strengthening the corporate sector's growth and introducing ED incentives into the welfare system.